Management of regeneration : choices, challenges and dilemmas - Diamond, John, 1954- (Routledge, 2005)
This book examines new forms of regeneration management while reflecting on the theoretical models of the past 20 years and focusing on partnership, sustainability, capacity building and community engagement and participation.